"Machetear": Surviving disability through mendicity in the North of Chile - Ferrante, Carolina (2018)
In the II Region of Chile, located at the North of the country and possessing the highest salaries throughout the country, there are many people with physical disabilities that resort to mendicity, which is a survival strategy locally known as machetear. According to spontaneous sociology, this scene is explained through cultural and moral protagonism that possesses solidarity towards people with disabilities in Chile. Even though this country has endorsed international human rights treaties, handout and generous disposition towards people with disability have not been subjected to exclusive problematization within a thematic unit. While reporting the results of a qualitative research carried out in this space, this article analyses the social conditions regarding the possibility of this interaction and identifies the perceptions and dispositions awaken by a disabled body begging within citizenship. It also makes the denigrating effects of these social responses towards ways of living with a disability visible. The corpus comprises content analysis of the main disability laws, non-participant observations of the interaction and 47 semi-structured interviews to people with physical disabilities that live through mendicity in the region, which are the key actors as regards disability, and Chileans who donate alms or not.